The γ-tubulin-specific inhibitor gatastatin reveals temporal requirements of microtubule nucleation during the cell cycle - Chinen, Takumi; Liu, Peng; Shioda, Shuya; Gunzelmann, Judith; Cerikan, Berati; Lin, Dennis Tien-chen; Gruss, Oliver; Hayashi, Yoshiki; Takeno, Haruka; Shima, Tomohiro; Okada, Yasushi; Hayakawa, Ichiro; et al. (Nature Communications, 2015)
Inhibitors of microtubule (MT) assembly or dynamics that target α/β-tubulin are widely exploited in cancer therapy and biological research. However, specific inhibitors of the MT nucleator γ-tubulin that would allow testing temporal functions of γ-tubulin during the cell cycle are yet to be identified. By evolving β-tubulin-binding drugs we now find that the glaziovianin A derivative gatastatin is a γ-tubulin-specific inhibitor. Gatastatin decreased interphase MT dynamics of human cells without affecting MT number. Gatastatin inhibited assembly of the mitotic spindle in prometaphase. Addition of gatastatin to preformed metaphase spindles altered MT dynamics, reduced the number of growing MTs and shortened spindle length. Furthermore, gatastatin prolonged anaphase duration by affecting anaphase spindle structure, indicating the continuous requirement of MT nucleation during mitosis. Thus, gatastatin facilitates the dissection of the role of γ-tubulin during the cell cycle and reveals the sustained role of γ-tubulin.
Gesehen am 30.11.2020